Characteristic Modeling and Control of Servo Systems with Backlash and Friction. (19th February 2014) - Wu, Yifei; Wang, Zhihong; Li, Yuanyuan; Chen, Wei; Du, Renhui; Chen, Qingwei
Abstract : A novel approach for modeling and control of servo systems with backlash and friction is proposed based on the characteristic model. Firstly, to deal with friction-induced nonlinearities, a smooth Stribeck friction model is introduced. The backlash is modeled by a continuous and derivable mathematical function. Secondly, a characteristic model in the form of a second-order slowly time-varying difference equation is established and verified by simulations. Thirdly, a composite controller including the golden-section adaptive control law and the integral control law is designed and the stability of the closed-loop system is analyzed. The simulation and experimental results show that the proposed control scheme is effective and can improve the steady-state precision and the dynamic performance of the servo system with backlash and friction.